The Future of Relations between Indonesia and the Middle East Region in Terms of Geopolitics as Indonesia's 2020-2024 Strategic Plan - TUTUKANSA, Aldho Faruqi (Journal of Political And Legal Sovereignty, 2023)
Purpose - This research examines the future relations between Indonesia and the middle east region regarding geopolitics as Indonesia's 2020-2024 strategic plan.Methodology - This study is qualitative. This research is a live case study that is used on a legal issue that has not ended or is currently happening, as well as conducting an extensive review of existing literature, scholarly articles, books, reports, and policy documents related to Indonesia's strategic plan, geopolitics, and the Middle East region. Analyze and synthesize the information to identify trends, perspectives, and potential future scenarios.Findings - The Middle East Region has various problems that occur in various aspects. However, the problems that occur are still said to be unable to be resolved by both parties alone but require one of the parties to participate in paving the way for peace between the Arab countries. Indonesia is considered capable of being a mediator because of the principles they carry out, namely a Free and Active Foreign Policy, close and harmonious relations between Indonesia and the Middle East Region in all aspects, and a continuous feeling of sympathy for one another.Implication - Foreign relations in the Middle East Region are included in the Strategic Plan by the Ministry of Foreign Affairs of the Republic of Indonesia as the primary goal in enhancing world peace based on the fourth paragraph of the Preamble of the 1945 Constitution of the Republic of Indonesia. Indonesia's geopolitical concept indeed has led and can be carried out specifically concerning the interaction of relations with countries in the Middle East Region.